Grading and Reporting Health and Health Disparities - Bridget C. Booske, PhD; Angela M. K. Rohan, PhD; David A. Kindig, MD, PhD; Patrick L. Remington, MD, MPH (Centers for Disease Control and Prevention, 2010)
Report cards are widely used in health for drawing attention to performance indicators. We developed a state health report card with separate grades for health and health disparities to generate interest in and awareness of differences in health across different population subgroups and to identify opportunities to improve health. We established grading curves from data for all 50 states for 2 outcomes (mortality and unhealthy days) and 4 life stages (infants, children and young adults, working-age adults, and older adults). We assigned grades for health within each life stage by sex, race/ethnicity, socioeconomics, and geography. We also assigned a health disparity grade to each life stage. Report cards can simplify complex information for lay audiences and garner media and policy maker attention. However, their development requires methodologic and value choices that may limit their interpretation.